Jiedu Granule Combined with Transcatheter Arterial Chemoembolization and Gamma Knife Radiosurgery in Treating Hepatocellular Carcinoma with Portal Vein Tumor Thrombus. (25th June 2019) - Wang, Jianchu; Luo, Jinhong; Yin, Xiaolan; Huang, Wei; Cao, Huangming; Wang, Guilin; Wang, Jincheng; Zhou, Jun
Abstract : Background . The potential advantages of Jiedu granule (a compound Chinese herbal medicine) combined therapeutic strategies compared with non-Jiedu granule therapeutic strategies for hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) remain unclear. Thus, the purpose of the study was to investigate the safety and efficacy of Jiedu granule for HCC with PVTT. Methods . We retrospectively reviewed the clinical data of 190 patients (94 for non-Jiedu and 96 for Jiedu) with HCC and PVTT from March 2012 to October 2016. Patients were followed up by outpatient examination and telephone till November 2018. Results . It was statistically insignificant between the two groups in baseline characteristics. Procedure-related adverse events (AEs) were observed and compared and most of them were not serious which were easily controlled or subsided naturally. No AE-induced death happened. The median overall survival (OS) rates in the single TACE plus GKR and Jiedu granule combined group were 11.3 months (95% CI: 9.168-13.435) and 15.8 months (95% CI: 13.244-18.339), respectively ( p = 0.00047). Conclusions . Jiedu granule combined with TACE plus GKR is safe in HCC patients with PVTT and this Chinese herbal medicine is worthy to be promoted because of better prognosis which needs further research.